PELAKSANAAN PROGRAM PENINGKATAN PRODUKSI PERTANIAN OLEH BALAI PENYULUHAN PERTANIAN (BPP) DI DESA SUNGAI SORIK KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Orben Mahendra; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Implementation is an action or implementation of a plan that has been prepared in detail, implementation is usually carried out after the plan is considered ready. In simple terms implementation can be interpreted as application. The agricultural extension program according to Law No. 16 of 2006 is a written plan that is systematically arranged to provide directions and guidelines as a means of controlling the achievement of extension objectives. Based on the agricultural extension program formed by the Agricultural Extension Center (BPP) of Kuantan Hilir Seberang District, Kuantan Singingi Regency in 2019 that there are several agricultural extension programs in the Sungai Sorik Village area, Kuantan Hilir District which is guided by Minister of Agriculture Regulation Number: 25/PERMENTAN/OT .140/5/2009 Concerning Guidelines for Preparation of Agricultural Extension Programs. That the extension program was formed on the basis of the aspirations of farmers and farming communities in accordance with the potential of the Sungai Sorik Village area. This study aims to determine the implementation of the Agricultural Production Increase Program by the Agricultural Extension Center in Sungai Sorik Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency in 2021 and also to find out the inhibiting factors for the Agricultural Production Increase Program in Sungai Sorik Village. Research results and discussion Developing extension programs, Carrying out counseling according to the program, Providing and disseminating information on technology, Developing farmer institutions, Increasing the capacity of PNS, Self- Help and Private extension workers, The learning process through piloting and Development of farming capital. Agricultural extension activities contained in the Agricultural Extension Program are still uneven in the assistance available in Sungai Sorik Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency, such as low Human Resources (HR) and a lack of extension workers. Keywords: Program Implementation, Agricultural Extension Center